Biomechanics of sport and exercise - McGinnis, Peter Merton 1954- (Human Kinetics, 2020)
By providing mechanics before functional anatomy, the book helps students understand forces and their effects before studying how body structures deal with forces. Students will learn to appreciate the consequences of external forces, how the body generates internal forces to maintain position, and how forces create movement in physical activities. This practical approach combines clear illustrations, sample calculations, and encouragement for active learning. Emphasis is on the basics, including improved descriptions of conversions and an expanded explanation of the assumption of point mass when modeling objects. There is new content on deriving kinematic data from video or film and the use of accelerometers in monitoring physical activity, provides a web resource, and review questions and problem sets